A reflective perspective for the teaching-learning process of the discipline FLT methodology at “Félix Varela” Pedagogical University - García Cabrera, Sirelda; Morales Rumbaut, Diana Rosa (Varela Journal, 2012)
One of the crucial factors in the success of learning anything depends on what the learners themselves bring to the learning situation. As psychologists assert, learning is more efficient when the learner interacts with what has to be learned in a particular situation. Following this assumption, one of the latest tendencies in teacher’s education (teacher training and teacher development) is based on a reflective model. The philosophy behind this approach is to provide teachers with a controlled teaching experience and a chance to consider the nature of teaching thoughtfully and objectively (Richards, Jack C. Longman Dictionary of Language Teaching and Applied Linguistics; 1997). Teachers of Foreign Language Teaching (FLT) Methodology at “Félix Varela” Pedagogical University have experienced the need to introduce reflective teaching as the approach of the subject, considering that it is a good way to improve classroom practices and the theories behind them. Therefore, a reflective teaching model was put into practice taking into account three areas of reflection and the results have been successful. The present paper is intended to exemplify how to integrate knowledge, practice and reflection as essential elements in FLT Methodology.